Sex and Male Circumcision: Women’s Preferences Across Different Cultures and Countries: A Systematic Review - Brian J. Morris, DSc, PhD; Catherine A. Hankins, MD, PhD; Eugenie R. Lumbers, MD, DSc; Adrian Mindel, MD; Jeffrey D. Klausner, MD, MPH; John N. Krieger, MD; Guy Cox, MA, DPhil (Sexual Medicine, 2019)
Introduction: Women’s choices for a sexual partner are influenced by numerous personal, cultural, social, political and religious factors, and may also include aspects of penile anatomy such as male circumcision (MC) status. Aim: To perform a systematic review examining (i) whether MC status influences women’s preference for sexual activity and the reasons for this, and (ii) whether women prefer MC for their sons. Methods: PRISMA-compliant searches were conducted of PubMed, Google Scholar, Embase, and the Cochrane Database of Systematic Reviews. Articles that met the inclusion criteria were rated for quality using the SIGN system. Results: Database searches identified 29 publications with original data for inclusion, including 22 for aim (i) and 4 of these and 7 others pertaining to aim (ii). In the overwhelming majority of studies, women expressed a preference for the circumcised penis. The main reasons given for this preference were better appearance, better hygiene, reduced risk of infection, and enhanced sexual activity, including vaginal intercourse, manual stimulation, and fellatio. In studies that assessed mothers’ preference for MC of sons, health, disease prevention, and hygiene were cited as major reasons for this preference. Cultural differences in preference were evident among some of the studies examined. Nevertheless, a preference for a circumcised penis was seen in most populations regardless of the frequency of MC in the study setting. Conclusion: Women’s preferences generally favor the circumcised penis for sexual activity, hygiene, and lower risk of infection. The findings add to the already well-established health benefits favoring MC and provide important sociosexual information on an issue of widespread interest.Morris BJ, Hankins CA, Lumbers ER, et al. Sex and Male Circumcision: Women’s Preferences Across Different Cultures and Countries: A Systematic Review. Sex Med 2019;7:145–161. Key Words: Male Circumcision, Female Sexual Pleasure, Female Sexual Activity, Vaginal Intercourse, Fellatio, Hygiene, Disease Risk, Parental Decision